The Model of Culture for Overcoming Human Resource Resistance to Change (Isfahan Department of Education) - Hasanzadeh, Seifolah; Mehtari Arani, Mohammad; Kianoush, Davud (Future of Work and Digital Management Journal, 2024)
The aim of this study was to present a model of culture for overcoming human resource resistance to change in the Isfahan Department of Education. From the perspective of purpose, this research is applied, and in terms of methodology, it is descriptive–analytical. The research method was mixed and conducted in two qualitative and quantitative phases. The statistical population in the qualitative phase consisted of 20 academic experts and executive managers in the education sector, who were selected through theoretical and snowball sampling until theoretical saturation was reached at the eleventh participant. The data collection instrument in the qualitative phase was a semi-structured interview, and data analysis was carried out using the grounded theory method. The quantitative phase followed a survey strategy using a questionnaire derived from the qualitative model. After confirming its validity and reliability, the model was subjected to empirical validation. The statistical population in the quantitative phase included managers and staff members of the Isfahan Department of Education, and the statistical sample consisted of 213 participants selected using stratified random sampling. The findings of the qualitative phase were presented in the form of a six-component paradigmatic model including causal, contextual, intervening, strategic, core, and consequential categories. In the quantitative phase, the causal paths and relationships among external and internal constructs in the structural model were confirmed through confirmatory factor analysis. The results obtained from AMOS software showed that the factor loadings in the paradigmatic model were higher than 0.6, and the fit indices (GFI, AGFI, CFI, and NFI) in the proposed model exceeded 0.9. Therefore, the research data exhibited a good fit with the factorial structure of the scale. Consequently, it can be concluded that by utilizing an appropriate organizational culture to foster a positive attitude among human resources toward change, it is possible to establish new orientations within organizations.